GOD OF MERCY, PEOPLE OF MERCY: THE YEAR OF MERCY AND THE MISSION OF THE CHURCH - BEVANS, Stephen B. (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2017)
The paper offers a missionary interpretation of Mercy. Mercy is presented as a visible and effectively active aspect of the essence of God, who is love (1John 4:8, 16). It is an attribute of God Who created the world, the creation being God’s first act of mission. Then Mercy is a reality in the history of Israel, where it takes a human face in the person of Jesus of Nazareth. In Pope Francis’s reflection, Jesus Christ is incarnate Mercy, or the face of mercy. The great mercy of God does not stop with simply having mercy on us, but He takes us in the heart of Mercy and makes us a community of mercy. Christians, as mercy-bearing disciples, need to constantly discern where God’s mercy is at work and beckons them to work in today’s Australian context: showing mercy to migrants and refugees, showing mercy to victims and perpetrators, and showing mercy to God’s creation.